2021
DOI: 10.1007/s11060-021-03793-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the updated renal graded prognostic assessment (GPA) for patients with renal cancer brain metastases treated with gamma knife radiosurgery

Abstract: Introduction: Prognosis of patients with brain metastasis (BM) from renal cell carcinoma (RCC) is relevant for treatment decisions and can be estimated with the Renal Graded Prognostic Assessment (GPA). The aim of this study is to validate the updated version of this instrument in a cohort treated with Gamma Knife radiosurgery (GKRS) without prior local intracerebral therapy. Methods: Between 2007 and 2018, 100 RCC patients with BM were treated with GKRS. They were categorized according to the updated Renal GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Very recently, van Ruitenbeek et al reported the validity of the Renal GPA system based on a relatively small number of patients, 106 renal cancer patients whose BMs were treated with gamma knife SRS. They described significant post-SRS MST differences between two pairs of subgroups, 0.0-1.0 (3.0 months) vs 1.5-4.0 (11.0, p=0.01) and 0.0-3.0 (6.0) vs 3.5-4.0 (20.0, p=0.01) [26]. However, they did not report post-SRS MST differences between three pairs of neighboring subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, van Ruitenbeek et al reported the validity of the Renal GPA system based on a relatively small number of patients, 106 renal cancer patients whose BMs were treated with gamma knife SRS. They described significant post-SRS MST differences between two pairs of subgroups, 0.0-1.0 (3.0 months) vs 1.5-4.0 (11.0, p=0.01) and 0.0-3.0 (6.0) vs 3.5-4.0 (20.0, p=0.01) [26]. However, they did not report post-SRS MST differences between three pairs of neighboring subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 95% CIs of the MSTs of each subgroup were not provided. Regarding pre-SRS clinical factors, they reported age, KPS, the blood hemoglobin level and time from primary cancer to BM detection to significantly impact to the survival of patients [26] .…”
Section: Discussionmentioning
confidence: 99%